Efeito de diurético ou bloqueador do receptor da angiotensina II sobre a pressão arterial central em pacientes com pré-hipertensão e hipertensão arterial estágio 1 - Fernandes, Letícia Aparecida Barufi (2015)
Background: Arterial Hypertension (AH) is defined by the conformation of systolic blood pressure (SBP) greater than 140 mmHg and / or diastolic blood pressure (DBP) greater than 90 mmHg. The Joint National Committee VII takes into account the prehypertension stage, characterized by arterial pressure (SBP 120-139 and / or DBP 80-89 mmHg, expression of great interest related to primary prevention. Objective: To assess the effect of treatment with thiazide diuretics or low-dose angiotensin II receptor blocker on central blood pressure and arterial stiffness in pre-hypertensive patients and hypertensive stage 1. Patients and Methods: Patients aged between 30 and 70 years were evaluated from January 2011 to September 2014. The groups were divided into pre-hypertensive (PHA) and stage 1 hypertensive (HA1), in whom the PHA was treated with Chlorthalidone + Amiloride or Placebo, and the HA1 with Chlorthalidone + Amiloride or Losartan; all in low doses. The central systolic blood pressure (PASC) was evaluated by means of Applanation Tonometry during periods of randomization; 6 months and 12 months of treatment. Statistical analysis was performed to compare the PASC behavior in PHA and HA1 patients, ANOVA with Dunets correction was applied in 6-month and 12-month phases. Results: The mean age of the group of pre-hypertensive patients was 52.33 ± 9.01 and in the hypertensive group was 54.0 ± 8.02. The mean systolic and diastolic pressure in the PHA was 125.80 ± 5.93 and 80.71 ± 5.49 and in HA1 was 139.0 ± 7.41 and 89.76 ± 6.59. Statistically significant reduction in central systolic pressure and Augmentation Index 75 was observed, after 12 months of pharmacological treatment in PHA patients. Conclusion: Treatment with active Chlorthalidone + Amiloride or Losartan at low doses reduces the central pressure in adults with hypertension stage 1 from the sixth month of active treatment. In hypertensive individuals showed a decrease in central systolic pressure and Augmentation Index 75, after twelve months of treatment.